Strong Disagreements West-Moscow on the Future of the World After World War II - Malia, Alban (European Journal of Multidisciplinary Studies, 2020)
The European continent after the end of World War II was completely destroyed. A destruction of such proportions was not even done in the 30-year War three hundred years ago, not even in the Napoleonic wars of the 19th century. Now the victors had to prepare the treaties. This did not turn out to be a simple task. For the first time the Council of Foreign Ministers of the victorious countries met in London from September 11 until October 2, 1945. The first problem faced by this council was the opposition of Soviet Foreign Minister Vyacheslav Molotov to accept France and China as allies. France was dissatisfied with the Soviet move and again felt excluded from major decisions. US President Harry Truman appealed directly to Stalin, but the latter did not respond. The Western allies proved determined. They would not allow any of their allies to be excluded from Soviet desires. This act was also the first disagreement between the Western foreign ministers and the Soviet foreign minister.